Mindfulness Affects the Level of Psychological Distress in Patients With Lung Cancer via Illness Perception and Perceived Stress: A Cross-Sectional Survey Study - Tian, Xu; Tang, Ling; Yi, Li-Juan; Qin, Xiao-Pei; Chen, Gui-Hua; Jiménez-Herrera, Maria F. (Frontiers in Psychology, 2022)
Purpose The aims of the study were first to investigate the association between illness perception and psychological distress and second to determine whether mindfulness affects psychological distress via illness perception and perceived stress in patients with lung cancer. Methods Among 300 patients with lung cancer who participated in this cross-sectional study, 295 patients made valid responses to distress thermometer (DT), the Five Facet Mindfulness Questionnaire (FFMQ), the Brief Illness Perception Questionnaire (B-IPQ), and the Perceived Stress Scale (PSS) between January and July 2021. The possible pathways of mindfulness affecting psychological distress were analyzed based on the structural equation modeling analysis. Results A total of 24.4% patients with lung cancer had DT > 4. Illness perception (β = 0.17, p = 0.002) and perceived stress (β = 0.23, p < 0.001) had a direct effect on psychological distress. Mindfulness had a direct effect on illness perception (β = −0.16, p = 0.006) and mindfulness indirectly influenced psychological distress (β = −0.04, p = 0.009) through affecting illness perception alone or simultaneously affecting both the illness perception and perceived stress in patients with lung cancer. Conclusion Lung cancer suffered from varying levels of psychological distress. Mindfulness may alleviate psychological distress by reducing the level of illness perception and perceived stress. We suggest developing a comprehensive factor model to clarify potential mechanisms of mindfulness on psychological distress due to the very low effect of mindfulness on psychological distress via illness perception and perceived stress.